Ultrasonografia dopplerowska z obrazowaniem przepływu krwi w kolorze (USG-kolor Doppler) w diagnostyce okulistycznej – doświadczenia własne i przegląd literatury - Ustymowicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Color Doppler ultrasound examinations are effective and very useful to differentiate and diagnose ocular and orbital diseases. In the paper some aspects of these examinations are discussed: technique, examined vessels, blood flow parameters. Special attention is paid to patient’s safety, drawbacks and limitations of presented technique.